1999
DOI: 10.1007/s101510050015
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous, combined sclerotherapy and rubber band ligation of haemorrhoids

Abstract: We present the results of combined, simultaneous application of sclerotherapy and rubber band ligation during one session in patients with symptomatic second-degree haemorrhoids. Between 1993 and 1996, 83 consecutive outpatients with second-degree haemorrhoids underwent simultaneous rubber band ligation of larger (primary) piles and sclerotherapy of smaller (secondary) piles. The treatment was successful, and the symptoms were controlled in 88% of the patients. The overall incidence of complications was 9.2%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Five studies [ 33 , 34 , 35 , 36 , 37 ], mainly retrospective ( Table 3 ), have been published in the literature about the concomitant use of SCT with RBL in the treatment of HD, but with different technical details and omitting important information for a fair comparison. All authors used oil-based sclerotizing agents, often injected into the submucosal plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies [ 33 , 34 , 35 , 36 , 37 ], mainly retrospective ( Table 3 ), have been published in the literature about the concomitant use of SCT with RBL in the treatment of HD, but with different technical details and omitting important information for a fair comparison. All authors used oil-based sclerotizing agents, often injected into the submucosal plane.…”
Section: Discussionmentioning
confidence: 99%
“…Chew et al reported a reverse approach, with SCT firstly applied in the hemorrhoidal nodule to facilitate the banding [ 33 ]. Kanellos et al both in their observational study [ 34 ] and in their prospective randomized trial [ 35 ] ligated larger hemorrhoidal nodules with a rubber band, injecting the sclerosant agent into the minor nodules.…”
Section: Discussionmentioning
confidence: 99%
“…However, as we already highlight in our article, “concomitant” does not imply “combined”. Two of these studies reported the selective use of RBL or Sclerotherapy in different nodules in the same patient [ 4 , 5 ]; another study described the use of sclerotherapy as the first step to reduce the volume of the hemorrhoidal nodule which is then treated by RBL [ 6 ]. Regarding the two oldest studies, one reported a technique with unclear steps [ 7 ], and another mentioned a “modified” RBL as a part of the procedure [ 8 ].…”
mentioning
confidence: 99%
“…They are low‐risk, inexpensive, repeatable and can be performed as office‐based procedures [2,3]. The simultaneous combined use of the two techniques may improve symptom control and long‐term results [4,5]. However, no studies in the literature describe the use of 3% polidocanol foam as a sclerotizing agent in combination.…”
mentioning
confidence: 99%